71°- domain wall in cubic crystal with photoinduced magnetic anisotropy - Antoniuk, O.A.; Kovalenko, V.F.; Tychko, O.V. (Functional Materials, 2004)
The influence of photoinduced anisotropy on Bloch 71°-domain wall in cubic magnetically ordered (100) crystal with negative constant of cubic magnetic anisotropy is studied. Equilibrium domain wall parameters (the surface energy density, orientation, and effective width) of the- wall have been found as functions of parameters (the constant value and easy axis orientation) of the photoinduced magnetic anisotropy. The energy density of the domain wall has been shown to be able both to increase and decrease, depending on the crystal irradiation conditions.